Effect of the Big Five Personality on the intention to use mHealth applications among the Chinese elderly: a national-based study - Chang, Jinghui; Li, Anqi; Yang, Xixi; Li, Chunnan; Mai, Yanshan; Zhang, Dayi; Yan, Wende; Wu, Yibo; Chen, Jiangyun (Frontiers in Psychology, 2025)
BackgroundMobile health applications may provide potential tools to support healthy aging. Promoting mHealth use by the elderly remains an imperative to realize health improvement.ObjectiveThe research aimed to identify the relationship between personality traits and the intention to use mHealth applications among the elderly in mainland China.MethodsUsing a multi-stage sampling method, a cross-sectional survey of 3,712 older adults across China was obtained out of 3,721 (validity rate was 99.76%) in 2022. The effect of personality on the intention to use mHealth applications among older adults was analyzed by multiple linear regression. The independent variable was the personality, using the short version of the Big Five Personality Inventory (BFI-10). The dependent variable was the intention to use the mHealth applications, measured using a sliding scale. Moderators included demographic characteristics and psycho-social variables measured by the Perceived Social Support Scale, the Family Health Scale, and the Health Literacy Scale.ResultsThe Chinese older adults’ intention to use mHealth applications scored (63.31 ± 25.09). Out of the five traits, extraversion, agreeableness, and openness exerted significant effects. Higher scores of extraversion (β=0.59, t = 1.99, p<0.05) and openness (β=1.87, t = 6.07, p<0.01) contributed to the intention to use mHealth applications. Conversely, higher agreeableness scores (β= − 1.05, t = −3.12, p<0.01) related to lower intention.ConclusionThe elderly with high extraversion, openness, and low agreeableness are more willing to adopt mHealth applications in China. Healthcare professionals and mHealth device developers can make personalized and accurate interventions for the elderly with different personalities.